Constructing Inclusive Higher Education: A Grounded Theory Study of Faculty Experiences with Disability Accommodation in Pakistani Universities - Dr. Tahira Batool Bokhari; Dr. Faisal Anis; Adil Shahzad (Research Journal of Psychology, 2025)
The present, grounded theory study explored faculty perceptions for fostering the implementation of disability accommodation at Pakistani universities to develop an integrated understanding of the determinants governing inclusive practices in higher education. Qualitative data were analyzed using constant comparative methods using MAXQDA software for data management and were used to collect data through semi-structured interviews with 20 university faculty members (5 each from 4 major universities in Pakistan). As illustrated in the emergent grounded theory model, the complex interplay of knowledge and awareness, challenges, strategies, and attitudinal shifts serve to shape faculty experiences. Such findings highlight the need for support in terms of both institutional avenues and resources and sensitivity training for better faculty practices and development in this area. In conclusion, this study contributes to the scarce literature available on the topic of disability accommodation, particularly from the Pakistan context, with implications that may help promote better equity and accessibility in various educational systems. The importance of the fundamental right to education of persons with disabilities should be convinced by this study, shared by all those stakeholders of higher education in Pakistan who readmit and need to improve practice around access to higher education for disabled students.